The Availability Of A Legal Structure For The Establishment Of Electronic Banks In Syria - محمود, يوسف; حمودة, نوار (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Aim to introduce e-banking and highlight the advantages of this type of banking and clarify its flaws in addition to legislation, laws, technologies and the physical structure necessary for its application in the Syrian reality. In addition to questions about the application of electronic banking, here comes the scientific methodology for research, which was theoretically represented in studying the experiences of some Arab countries and analyzing some previous studies and from the field view with a field study of A soft part of Syrian society, including administrators in public and private banks, The most important results of the research were Syrian banks close and not identical to the surrounding regional and international banks in terms of providing traditional services to banks. As for the applied part of electronic banking services, it is a small part in relation to electronic banking services applied to regional and international banks.